The research of the formation of eating and personal hygiene skills among children with moderate and severe mental disability - Haletska, Yuliya (Special Education, 2022)
The article analyzes the results of the study of the formation of eating and personal hygiene skills among children with moderate and severe intellectual disabilities. The main directions of correctional work on the formation of self-care skills among children with intellectual disabilities have been described: eating skills; personal hygiene skills; dressing and undressing skills, etc. It has been established that the success of the formation of domestic independence among children with moderate and severe intellectual disabilities is determined by compliance with such conditions, in particular, determining the actual level of the child’s needs, improving the content of work with children, using a variety of visual aids, forming of a positive attitude to household activities, the gradual weakening of control in order to increase the independence and activity of the child.
Keywords: child with intellectual disabilities; moderate and severe mental retardation; eating skills; personal hygiene skills; special institution